Security offset printing with twin colors by means of CMYF separation - Morić Kolarić, Branka; Žiljak Stanimirović, Ivana; Bak, Ivana (Journal of Print and Media Technology Research, 2023)
A new method of security printing is introduced in this work, thus creating highly protected documents by ink management in three spectrally separated ranges. A numerical experimental color setting has been developed, considering ink properties in three wave ranges: 200–400 nm, 400–700 nm and 700–1 000 nm. Separation is carried out with process and spot inks, aiming at concealing the graphic in visible spectrum. Such a graphic can be recognized instrumentally in the ultraviolet (F) and infrared (Z) spectra. Extending the Infraredesign method, the ultraviolet spectrum is included through the properties of the dark brown UV ink, thus giving fluorescent green in UV spectrum, while the absorption value is 38 % for parameter Z in the NIR spectrum. A separate, third image is visible by the naked eye. By algorithmic mixing of F-ink, having absorption properties in UV and IR ranges, a unique solution for the security printing of documents and valuables is accomplished. CMYF method differs from the CMYKIR method, since the K ink does not have the same properties, while their Z factor is completely different under the same printing conditions. With this new method – CMYF separation – formulations and standards are set for determining the differences between the original and the forgery.